Natural and redesigned wasp venom peptides with selective antitumoral activity - Torres, Marcelo D. T.; Andrade, Gislaine P.; Sato, Roseli H.; Pedron, Cibele N.; Manieri, Tania M.; Cerchiaro, Giselle; Ribeiro, Anderson O.; de la Fuente-Nunez, Cesar; Oliveira, Vani X., Jr. (Beilstein Journal of Organic Chemistry, 2018)
About 1 in 8 U.S. women (≈12%) will develop invasive breast cancer over the course of their lifetime. Surgery, chemotherapy, radiotherapy, and hormone manipulation constitute the major treatment options for breast cancer. Here, we show that both a natural antimicrobial peptide (AMP) derived from wasp venom (decoralin, Dec-NH2), and its synthetic variants generated via peptide design, display potent activity against cancer cells. We tested the derivatives at increasing doses and observed anticancer activity at concentrations as low as 12.5 μmol L−1 for the selective targeting of MCF-7 breast cancer cells. Flow cytometry assays further revealed that treatment with wild-type (WT) peptide Dec-NH2 led to necrosis of MCF-7 cells. Additional atomic force microscopy (AFM) measurements indicated that the roughness of cancer cell membranes increased significantly when treated with lead peptides compared to controls. Biophysical features such as helicity, hydrophobicity, and net positive charge were identified to play an important role in the anticancer activity of the peptides. Indeed, abrupt changes in peptide hydrophobicity and conformational propensity led to peptide inactivation, whereas increasing the net positive charge of peptides enhanced their activity. We present peptide templates with selective activity towards breast cancer cells that leave normal cells unaffected. These templates represent excellent scaffolds for the design of selective anticancer peptide therapeutics.
Keywords: breast cancer; decoralin; MCF-7 cells; peptide design; selective anticancer peptides; structure–activity relationships